'They were constantly on the losing side of things': the pedagogical power of an African-American teacher candidate bearing witness in teacher education. Issue 4 (4th July 2017) - Bryson, Brandy S.
Abstract: The stories of students and teacher candidates of Color (Just as singular racial/ethnic identities are capitalized (i.e. African-American, Asian, Latina, Native American etc.), I capitalize Color to honor the various identities that many 'non-white' people hold near and dear. I recognize the nuances in doing so- such as the reality that the term 'people of Color' actually erases identity while the term also highlights a shared experience (though also nuanced) of being 'non-white' in a white supremacist society.) hold powerful lessons and insights for teacher education programs and educational reform efforts. Yet, rarely do educators and policy-makers solicit or critically engage the educational narratives of these stakeholders. In particular, research confirms that we know little about how students' of Color educational experiences are impacted by race(ism) and culture and how those experiences subsequently inform their ideas about teaching. This study, framed by critical race theory (CRT), examines an African-American (African-American is used intentionally here as this is how Ariel identifies racially.) teacher candidate's racialized K-12 and postsecondary school experiences to more fully understand the connection between lived experience and developing teacher identity. Ariel's story reflects her own school experiences; her focus on her peers' school experiences when asked about her own; and how those experiences, informed by race and culture, contribute to her development of pedagogy. Analytical considerations illustrate that memory and remembrance, witnessing and bearing witness, and testimony are deliberate and powerful acts in the development of pedagogy and should be central to teacher education curriculum.